Genetic variation of innate immune genes in HIV-infected African patients with or without oropharyngeal candidiasis - Plantinga, Theo S. (2010)
BACKGROUND: The occurrence of oropharyngeal candidiasis (OPC) in combination with HIV disease progression is a very common phenomenon. However, not all HIV-infected patients develop OPC, even when they progress to low CD4+ T cell counts. Because T-cell immunity is defective in AIDS, the innate defence mechanisms are likely to have a central role in antifungal immunity in these patients. We investigated whether genetic variations in the innate immune genes DECTIN-1, TLR2, TLR4, TIRAP and CASPASE-12 are associated with the presence of OPC in HIV-infected subjects from East-Africa. METHODS: A total of 225 HIV patients were genotyped for several single nucleotide polymorphisms (SNP) and this was correlated with the occurrence of OPC in these patients. In addition, primary immune cells obtained from individuals with different genotypes were stimulated with C.albicans and cytokine production was measured. RESULTS: The analysis revealed that no significant differences in the polymorphism frequencies could be observed, although a tendency towards a protective effect on OPC of the DECTIN-1 I223S SNP was apparent. Furthermore, IFNγ production capacity was markedly lower in cells bearing the DECTIN-1 SNP I223S. It could also be demonstrated that the 223S mutated form of the DECTIN-1 gene exhibits a lower capacity to bind zymosan. CONCLUSION: These data demonstrate that common polymorphisms of TLR2, TLR4, TIRAP and CASPASE-12 do not influence susceptibility to OPC in HIV-infected patients in East-Africa but suggest an immunomodulatory effect of the I223S SNP on dectin-1 function and possibly the susceptibility to OPC in HIV patients.